THE DEVELOPMENT OF PENANG SHOP PRICE INDEX (PSPI) USING LASPEYRES HEDONIC PRICE MODEL - Jamaludin, Mohamad Hafiz; Ismail, Suriatini; Ismail, Norziha (PLANNING MALAYSIA, 2021)
The index is considered an important benchmark and is a decision-making tool in the financial and capital markets, as well as in the property market. In Malaysia, continuous monitoring of property price movements is important as almost half of banking exposure is on property. Further, NAPIC has published indicators displaying the performance of property such as MHPI and PBO-RI. However, indicators regarding the price of commercial property are still less widely published in Malaysia. This study was conducted to develop indicators related to the price of commercial property, especially to shop property. This study has focused on the state of Penang as a study area. The literature review methodology is used to identify existing methods and practices used in developing the index of commercial property both in Malaysia and internationally. In determining the appropriate form of hedonic functions for the development of PSPI, analysis of dependent and independent variables was performed. Meanwhile, the development of the index is based on the Laspeyres hedonic model which is the same as the development of MHPI and PBO-RI. The development of PSPI will be able to help the industry and investors to make decisions and benchmark the performance of shop. This is also one of the pilot studies in Malaysia to form an indicator of commercial property.